Effect of rosiglitazone on cardiac electrophysiology, infarct size and mitochondrial function in ischaemia and reperfusion of swine and rat heart - Siripong Palee (2018)
Rosiglitazone, a peroxisome proliferator-activated receptor γ agonist, has been used to treat type 2 diabetes. Despite debates regarding its cardioprotection, the effects of rosiglitazone on cardiac electrophysiology are still unclear. This study determined the effect of rosiglitazone on ventricular fibrillation (VF) incidence, VF threshold (VFT), defibrillation threshold (DFT) and mitochondrial function during ischaemia and reperfusion. Twenty-six pigs were used. In each pig, either rosiglitazone (1 mg kg -1) or normal saline solution was administered intravenously for 60 min. Then, the left anterior descending coronary artery was ligated for 60 min and released to promote reperfusion for 120 min. The cardiac electrophysiological parameters were determined at the beginning of the study and during the ischaemia and reperfusion periods. The heart was removed, and the area at risk and infarct size in each heart were determined. Cardiac mitochondria were isolated for determination of mitochondrial function. Rosiglitazone did not improve the DFT and VFT during the ischaemia-reperfusion period. In the rosiglitazone group, the VF incidence was increased (58versus10%) and the time to the first occurrence of VF was decreased (3 ± 2versus19 ± 1 min) in comparison to the vehicle group (P< 0.05). However, the infarct size related to the area at risk in the rosiglitazone group was significantly decreased (P< 0.05). In the cardiac mitochondria, rosiglitazone did not alter the level of production of reactive oxygen species and could not prevent mitochondrial membrane potential changes. Rosiglitazone increased the propensity for VF, and could neither increase defibrillation efficacy nor improve cardiac mitochondrial function. © 2011 The Authors. Journal compilation © 2011 The Physiological Society.